Beyond post-Christendom discipleship of the Evangelical Church in the United Kingdom: A study of the Gospel of Matthew in the transformissional and holistic perspective - Henry, Desmond (Verbum et ecclesia, 2021)
Discipleship has been, and continues to be, integral to the church’s strategy to simultaneously contribute towards the spiritual formation of its members and also fulfilling its mission. From the very outset of the church, Jesus demonstrated the centrality of discipleship through what he taught and practiced. However, as the United Kingdom moved into the post-Christendom era, the Evangelical Church has grappled with being effective in discipleship. Through a study in the Gospel of Matthew in the transformissional and holistic perspective, the article seeks to aid this vital part of the church’s strategy by suggesting a paradigm shift and reprioritisation of the discipleship emphasis.Intradisciplinary and/or interdisciplinary implications: The article will suggest a paradigm shift to the traditional discipleship discourse of post-Christendom era evangelical churches in the United Kingdom. The research will review Scripture, practical theology and interdisciplinary fields such as the influence of Christianity on health and family to establish a more holistically focussed and transformissional discipleship perspective.